2017
DOI: 10.1177/1947603517743000
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinically Relevant Improvement in Quality of Life and Clinical Outcomes 1 Year Postsurgery in Patients with Knee and Hip Joint Arthroplasties

Abstract: Objective To measure and identify the determinants of the outcomes after hip/knee arthroplasty (HA/KA) in patients with osteoarthritis during the first postsurgical year. Design In this prospective observational study, we evaluated the preoperative and postoperative (3, 6, and 12 months) outcomes of 626 patients who underwent HA (346 with median age 65 years, 59% female) or KA (280 with median age 66.5 years, 54% female) between 2008 and 2013. Generic and specific tools were used to measure health-related qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 74 publications
2
29
1
2
Order By: Relevance
“…Therefore, it is important to carefully evaluate the patient's benefits of these surgical interventions. In a previous study, we demonstrated fast (from 3 months), substantial, and shortterm benefits of HA and KA on parameters reflecting quality of life and health utility [10]. We have continued a 5-year follow-up of this large number of OA patients, from both genders, who underwent joint replacement of the knee or hip.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Therefore, it is important to carefully evaluate the patient's benefits of these surgical interventions. In a previous study, we demonstrated fast (from 3 months), substantial, and shortterm benefits of HA and KA on parameters reflecting quality of life and health utility [10]. We have continued a 5-year follow-up of this large number of OA patients, from both genders, who underwent joint replacement of the knee or hip.…”
Section: Introductionmentioning
confidence: 81%
“…Then, we performed secondary analyses seeking associations between these factors and good outcome using binary logistic backward regression modeling. Finally, as previously performed, we explored the profile of patients with long-term complications using the same statistical strategy [10]. The odds ratios (ORs) associated with each of the identified predictors were determined using logit regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 reported that skeletal muscle mass index is negatively associated with the Kellgren–Lawrence grade (K-L grade) of radiographic KOA. Given that low muscle mass is associated with greater functional impairment 17 and preoperative functional status predicts the functional recovery pattern, 18 , 19 potential sarcopenia in older people with KOA may affect post-surgery outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Over 90,000 THA and over 1.1 million TKA procedures were undertaken in 2018 in the UK, whilst in the US, incidence is estimated to grow to 572,000 THA and 3.48 million TKA procedures per annum by 2030 [2]. While these procedures are effective in improving pain and function [3][4][5][6][7], there is a risk of complications. The most common complications requiring readmission for hip arthroplasty are dislocation and infection, whereas infection dominates following knee arthroplasty [8,9].…”
Section: Introductionmentioning
confidence: 99%